Analysis of the Livelihood Shift of Sea Cucumber Fishermen on Local Economic Mobility in Sitardas Village - Mutiara Alkayakni Harahap; Riqzon Hasibuan; Husnul Yaqin Harahap (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Sitardas Village is located in Central Tapanuli Regency, a coastal area rich in marine resources, one of which is sea cucumbers (holothurians). Sea cucumbers have long been an ecologically and economically important commodity for the community, serving as the primary source of livelihood for fishermen. Sea cucumbers caught in Sitardas Village not only meet local market demand but also have significant potential in the global market, particularly in the export trade sector. Sea cucumber fishing is becoming increasingly common due to increasing demand. Given this potential, the urgency of this research is that it often faces various challenges. One such challenge is the decline in sea cucumber populations due to overexploitation. To address this issue, the aim of this research is to influence local economic mobility and how communities can adapt to these changes without compromising the sustainability of marine resources. Therefore, this analysis is crucial for providing strategic recommendations for managing natural resources sustainably while encouraging improved community welfare. This research is also expected to identify patterns of livelihood changes and their driving and inhibiting factors, so that interventions can be designed appropriately and support sea cucumber conservation efforts while strengthening the local economy in a sustainable manner.